Landscape of Participant-Centric Initiatives for Medical Research in the United States, the United Kingdom, and Japan: Scoping Review - Hamakawa, Nao; Nakano, Rumiko; Kogetsu, Atsushi; Coathup, Victoria; Kaye, Jane; Yamamoto, Beverley Anne; Kato, Kazuto (JMIR Publications, 2020)
BackgroundInformation and communication technology (ICT) has made remarkable progress in recent years and is being increasingly applied to medical research. This technology has the potential to facilitate the active involvement of research participants. Digital platforms that enable participants to be involved in the research process are called participant-centric initiatives (PCIs). Several PCIs have been reported in the literature, but no scoping reviews have been carried out. Moreover, detailed methods and features to aid in developing a clear definition of PCIs have not been sufficiently elucidated to date. ObjectiveThe objective of this scoping review is to describe the recent trends in, and features of, PCIs across the United States, the United Kingdom, and Japan. MethodsWe applied a methodology suggested by Levac et al to conduct this scoping review. We searched electronic databases-MEDLINE (Medical Literature Analysis and Retrieval System Online), Embase (Excerpta Medica Database), CINAHL (Cumulative Index of Nursing and Allied Health Literature), PsycINFO, and Ichushi-Web-and sources of grey literature, as well as internet search engines-Google and Bing. We hand-searched through key journals and reference lists of the relevant articles. Medical research using ICT was eligible for inclusion if there was a description of the active involvement of the participants. ResultsUltimately, 21 PCIs were identified that have implemented practical methods and modes of various communication activities, such as patient forums and use of social media, in the field of medical research. Various methods of decision making that enable participants to become involved in setting the agenda were also evident. ConclusionsThis scoping review is the first study to analyze the detailed features of PCIs and how they are being implemented. By clarifying the modes and methods of various forms of communication and decision making with patients, this review contributes to a better understanding of patient-centric involvement, which can be facilitated by PCIs. International Registered Report Identifier (IRRID)RR2-10.2196/resprot.7407